Matrix-Delivered Autologous Mesenchymal Stem Cell Therapy for Refractory Rectovaginal Crohn's Fistulas. Issue 5 (12th October 2019) - Lightner, Amy L; Dozois, Eric J; Dietz, Allan B; Fletcher, Joel G; Friton, Jessica; Butler, Greg; Faubion, William A
Abstract: Background: Crohn's rectovaginal fistulizing disease remains notoriously difficult to treat. A phase I clinical trial to evaluate the safety and feasibility of a novel protocol using a mesenchymal stem cell (MSC)–coated Gore Bio-A fistula plug for the treatment of medically and surgically refractory Crohn's rectovaginal fistulas was conducted. Methods: Five patients underwent an autologous subcutaneous adipose tissue harvest via a 2-cm abdominal wall incision at time of exam under anesthesia (EUA) with seton placement. MSCs were isolated, expanded, and impregnated on the plug. After 6 weeks, patients returned to the operating room for placement of the MSC-coated plug. The primary end points were safety and feasibility; the secondary end point was clinical and radiographic healing at 6 months. Results: Five female patients (median age [range], 49 [38–53] years) with a median disease duration (range) of 23 (7–34) years who were on biologic (n = 5) or combination therapy (n = 3) had successful harvest and expansion of MSCs and delivery of the Gore Bio-A plug. There were no serious adverse events or adverse events related to the MSCs or plug during the 6-month follow-up. At 6 months, 3 patients had complete cessation of drainage, and 2 had >50% reduction in drainage; all had a persistent fistula tract identified on magnetic resonance imaging and EUA at 6 months. Conclusions: Surgical placement of an autologous adipose-derived MSC-coated fistula plug in diverted patients with Crohn's rectovaginal fistulas was safe and feasible. All patients had a reduction in the size of their fistula tract, and 3 of 5 had cessation of drainage, but none achieved complete healing. This was a phase I clinical trial of autologous mesenchymal stem cells on a plug for rectovaginal Crohn's fistulas. Abstract : This was a phase I clinical trial of autologous mesenchymal stem cells on a plug for rectovaginal Crohn's fistulas.